PRESENCE OR ABSENCE OF STONE CELLS IN THE ROOTS OF INDIAN ACONITES: AN AID TO IDENTIFICATION OF SPECIES - Selvam, A. B. D. (Asian Journal of Pharmaceutical Research and Development, 2018)
The species of the genus Aconitum are commonly and collectively called Aconites in trade. Aconites are known to people since antiquity as deadly poisonous plants. They are being used world-wide either as an arrow poison to kill the wild animals illegally or to heal human beings legally. After detoxification of the roots of Aconites using conventional methods, they are being used in different traditional systems of medicine such as Chinese, Japanese, Nepalese, Ayurveda, Siddha, Unani and Tibetan, in addition to tribal and folk medicines. The roots of Aconites are highly exploited from wild sources and are traded illegally. Identification of traded roots of Aconites is a difficult task. To overcome this botanical problem, anatomical characters may be used. Sclereids, particularly brachysclereids are popularly known as stone cells because of their hardness. Stone cells protect other cells/tissues of the plants or plant parts. Since the presence of stone cells in plants is considered as one of the constant characters (marker characters), which may be very well utilized for identification or authentication of tuberous roots of Aconites. The present study highlights the presence or absence of stone cells (brachysclereids) in the tuberous storage roots of Indian Aconites as an aid for the identification or authentication at species level.